2012
DOI: 10.1590/s1678-77572012000500014
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a multi-layer infection control barrier on the micro-hardness of a composite resin

Abstract: ObjectiveThe aim of this study was to evaluate the effect of multiple layers of an infection control barrier on the micro-hardness of a composite resin. Material and MethodsOne, two, four, and eight layers of an infection control barrier were used to cover the light guides of a high-power light emitting diode (LED) light curing unit (LCU) and a low-power halogen LCU. The composite specimens were photopolymerized with the LCUs and the barriers, and the micro-hardness of the upper and lower surfaces was measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 21 publications
0
6
1
1
Order By: Relevance
“…According to the CDC Guidelines for infection control, LGs of LCU should be sterile before using it in every next patient. [ 4 12 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the CDC Guidelines for infection control, LGs of LCU should be sterile before using it in every next patient. [ 4 12 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 12 ] The HR should be more than 80% for composite resins that are adequately cured. [ 12 ] In the present study, all the barriers except LCGP showed HR more than 80% [ Table 3 ]. These results are in agreement with Sword et al ., who revealed only latex-based barriers significantly reduced curing of composite.…”
Section: Discussionmentioning
confidence: 99%
“…Usually, the degree of conversion of a composite resin is assessed by the hardness 27,28 and the hardness ratio, 29 the ratio between the upper and lower surface hardness values of a 2-mm-thick composite resin specimen. 8,30 However, in this study, the hardness of the lower surface of the DCRC was not measured because the thickness of the DCRC was controlled to 1.0 mm.…”
Section: Discussionmentioning
confidence: 99%
“…A few authors explored cling films as a form of infection control barrier. 3 -7 , 10 , 11 With the considerations of the research involving efficacy of a cling film as an infection-control barrier and microbial contamination, 11 , 12 as well as two-layer infection control barrier, 13 our study will explore the effect on light output and clinical efficacy of the cling film and compare with sleeves.…”
Section: Introductionmentioning
confidence: 99%